Republic of San Marino : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This Selected Issues paper for the Republic of San Marino analyzes options for managing systemic liquidity risk. The paper states that financial dollarization/euroization-as in the case of San Marino-or a currency board arrangement can complicate banking crisis management and increase the vulnerability of financial systems to liquidity shocks because they limit the ability of the monetary authority to act as a lender of last resort. The paper reviews the current pension system of San Marino, in comparison with other European pension systems, and analyzes its sustainability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet